The Expansion of the Railway and Environmental Changes: The Modern Configuration of the Argentine Pampas, c. 1870–1930 - Franca de Oliveira, Ana Marcela (2022)
One of the most striking transformation processes of the Anthropocene in Argentina is related to the occupation of the territory through agricultural activities and the arrival of the train from the mid-nineteenth century. The transformations of the Pampa biome are a typical case of socio-environmental transitions caused by the country´s entry into the global market. At the basis of agricultural expansion through the agro-export model was the idea of an "empty" territory. At the core of the Anthropocene is the homogenization of environments, from the introduction of exotic fauna and flora, technologies, cultures and ideas (modernity). This process of homogenisation implies the destruction of the heterogeneity of native ecosystems. These are aspects that will be discussed in our article. Considering socio-environmental analyses together with technological issues, our paper exemplifies the peculiarity of Argentina´s modernization process in the context of the Anthropocene.